Inequality and antibiotic resistance: A contractualist perspective. (18th August 2019) - Millar, Michael
Abstract: There are substantial inequalities associated with antibiotics and the determinants of their effectiveness, including the risk of exposure to antibiotic‐resistant microbes, access to relevant treatment advice, diagnostic facilities, risk of life‐threatening infectious disease, and access to antibiotics. Current arrangements (social, political, economic) allow inequalities in the distribution of antibiotic benefits and burdens. This article focuses on the justification of relevant inequalities from a contractualist perspective.